FREQUENCY OF CEREBELLOPONTINE ANGLE TUMOURS IN PATIENTS WITH TRIGEMINAL NEURALGIA - Afridi, Ehtisham Ahmed Khan; Khan, Shahbaz Ali; Qureshi, Waqar -ur-Rehman; Bhatti, Sajid Nazir; Muhammad, Gul; Mahmood, Shakir; Rehman, Abdur (Journal of Ayub Medical College Abbottabad, 2014)
Background: Though the classical type of trigeminal neuralgia is the most common type with the neurovascular conflict causing the symptoms, yet quite some patients have the secondary type of trigeminal neuralgia in which space occupying lesions are responsible for the symptoms. This study was conducted to determine the frequency of cerebellopontine angle tumours in patients presenting with complaints of trigeminal neuralgia. Methods: This case series descriptive study was conducted in the department of Neurosurgery, Ayub Medical College, Abbottabad, from January 2009 to January 2012. It included patients who presented with symptoms of trigeminal neuralgia. Patients were subjected to further radiological investigation like Computed Tomography (CT) and Magnetic Resonance Imaging (MRI) to look for secondary causes of trigeminal neuralgia. Results: Among the 134 patients with age ranges 13-64 (51±4.3) years of age, 78(58.2%) were females and 56 (41.7%) were males. Frequency of cerebellopontine angle tumours in patients was 14 (10.4%), among them epidermoid was most common lesion being present in 10 (7.4%) of patients and accounted for 75% of Cerebellopontine Angle tumours in these patients. Meningioma and vestibular schwanoma accounted for 2(1.4%) cases each. In secondary trigeminal neuralgia mean age of onset of symptoms was 39.5±5.2 years as compared to classic trigeminal neuralgia which is 53±2.1 years. Conclusion: Trigeminal Neuralgia can be a typical symptom in cerebellopontine angle tumours like epidermoid, especially in young patients, so all the patients with trigeminal neuralgia should be investigated for lesion in cerebellopontine region. Keywords: Trigeminal Neuralgia, Cerebellopontine Angle Tumours